Monetary accommodation of regional integration in Latin America - Ziegler, Lawrence F. (Austin : Bureau of Business Research, Graduate School of Business, University of Texas, 1971)
This book considers the economic problems in Latin America and suggested how it can be solved. It takes cognizance of the new problems accompanying each possible solution in its analysis and of the involvement of financial institutions on all levels of domestic, regional, and international.
Bibliography: p. 79-83.
usc 08/10/18
Loans
Keywords: Money; International economic integration; Latin America